Identifying endogenous and exogenous indicators to measure eco-innovation within clusters (2020)
Scientific and business environment literature shows that green, sustainable innovation or eco-innovation has proven to be a source of competitive advantage today. The industrial clusters, their dynamism, and the synergies created within them attract a lot of attention from the scientific community. However, to date, the joint study of these two concepts and, more specifically, the factors that drive eco-innovation specifically in a cluster, have not been studied in depth. This article models eco-innovation in industrial clusters, thus addressing this gap and proposing a model based on information gathered from the literature and a detailed analysis of behavior in relation to eco-innovation in di erent sectors. Results suggest that including eco-innovation variables and measures may have positive implications such as improvements at the strategic level and the reduction of costs and use of resources. An eco-innovation model for clusters is proposed. It considers eight key factors that seek to raise its competitive level by promoting eco-innovation within clusters. The model includes five internal factors that analyze business capabilities and three external factors that study the e ect of launching eco-innovative activities. This model could help the companies’ managers and those responsible for clusters in creating more successful strategies to increase competitiveness by enhancing eco-innovation. It could also serve as a guide for government entities in the performance of eco-innovative activities in economic sectors.